• Упростите выражение: (a^2-3a:a^2-6a+9-3a+9:a^2-9)*(1-3:a)

Ответы 1

  • ((a^2 - 3a) /(a^2 - 6a + 9) - (3a+9) / (a^2-9)) * (1 - 3 / a) = (a * (a - 3) / (a - 3) * (a - 3)) - (3 * (a + 3) / (a - 3) * (a + 3)) * ((a - 3) / a) = (a / (a - 3)) - (3 / (a - 3)) * ((a - 3) / a) = ((a - 3) / (a - 3)) * ((a - 3) / a) = (a - 3) * (a - 3) / (a - 3) * 3 = (a - 3) / 3.

    Ответ: (a - 3) / 3.

    • Автор:

      tasha41
    • 3 года назад
    • 0
  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years